Pembangunan video dokumentari pendidikan bagi mata pelajaran teknologi konkrit - Zakaria, Mohd Zaim (2004)
The purpose of this research is to create a Documentary Video cd. This is as a cosware for the Concrete Technology sub ject with a topic of Concrete Material Test (Laboratory: C2003) in teaching and learning process at Polytechnic. The Documentary Education VCD are evaluate from visual, audio and content elements and further more evaluation were done from interesting and understanding increase for student in learning when they used that Documentary Education VCD Around 32 respondents from sem 2 students in Civil Building Certificate course at polytechnic Sultan Abdul Halim Mu'adzam Shah, Jitra, Kedah. Questionnaire instrument were used to evaluate the Documentary Education VCD, which was produced. The data was analyzed using statistic method from Statistical Packages for Social Sciences (SPSS) version 11.0 which include percentages, min score and standard devition. Research result are positif that is the min score for each item from section B exceeding 3.8. This shows the respondent agree with the Documentary Education VCD produced at Polytechnic. The researcher hopes that this research can be improvement for a better research for those who are interest to do the same research in the future.